Paradoxes of the Sharing Economy: A pandemic perspective - Davlembayeva, Dinara; Papagiannidis, Savvas (Senate Hall, 2021)
The sharing economy was expected to bring sustainable transformations towards social welfare, economic growth and environmental preservation. Yet it has not always lived up to these expectations. After the COVID-19 pandemic, societal benefits may become more elusive, considering the social and economic disruption that the pandemic has caused. The pandemic has made rethinking the sustainable pathways of platform-based entrepreneurship even more pressing. This conceptual paper starts by discussing the social, economic and environmental paradoxes of the sharing economy before the pandemic. The paper explores the roots of contradictory insights by analysing the role of normative, economic and digital regulatory mechanisms governing relations within platforms. In turn the paper analyses the effect of COVID-19 on platform regulatory mechanisms and their potential impact on the social, economic and environmental dimensions of sustainability. The paper contributes to our understanding of the mechanisms underpinning sharing economy practices and can help probe the future of the sharing economy.
Keywords: sharing economy|entrepreneurship|sustainability|paradoxes|COVID-19|pandemic